2021
DOI: 10.3389/fvets.2021.674557
|View full text |Cite
|
Sign up to set email alerts
|

The Irish Programme to Eradicate Bovine Viral Diarrhoea Virus—Organization, Challenges, and Progress

Abstract: A mandatory national Irish bovine viral diarrhoea (BVD) eradication programme, coordinated by Animal Health Ireland, commenced in 2013. Key decisions and programme review are undertaken by a cross-industry Implementation Group (BVDIG) supported by a Technical Working Group. Ear notch tissue is collected from all new-born calves using modified official identity tags, supplemented by additional blood sampling, including for confirmatory testing of calves with initial positive results and testing of their dams. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 42 publications
0
13
4
Order By: Relevance
“…36.4% of vaccinating beef herds and 25.8% of dairy used live vaccine. This is in contrast with details of annual vaccine sales, obtained through a market research company 3 , that showed that total doses sold in Ireland have experienced a 32.2% decrease since 2016/17, with sales of inactivated vaccines predominating (14). However, when the length of time in years that the vaccination regimen has been in place is analysed, between 42.3 and 49.4% of investigated herds through the years indicated they had been vaccinating for <1 year, which is considered to reflect the initiation of a vaccination regimen on the basis of the PVP's recommendation following the disclosure of the positive result.…”
Section: Discussioncontrasting
confidence: 69%
See 4 more Smart Citations
“…36.4% of vaccinating beef herds and 25.8% of dairy used live vaccine. This is in contrast with details of annual vaccine sales, obtained through a market research company 3 , that showed that total doses sold in Ireland have experienced a 32.2% decrease since 2016/17, with sales of inactivated vaccines predominating (14). However, when the length of time in years that the vaccination regimen has been in place is analysed, between 42.3 and 49.4% of investigated herds through the years indicated they had been vaccinating for <1 year, which is considered to reflect the initiation of a vaccination regimen on the basis of the PVP's recommendation following the disclosure of the positive result.…”
Section: Discussioncontrasting
confidence: 69%
“…Of the investigated herds, 15.7% reported a retained PI animal as the plausible source of infection, with this being more frequent in beef (18.3%) than dairy herds (12.4%). Retained animals were one of the key challenges in the early years of the programme (14,35). The introduction of a series of measures has largely resolved this issue, including graduated financial supports for their removal, movement restrictions, ongoing programme communications and the input of PVPs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations